Studi tentang Pengetahuan, Sikap dan Tindakan Ibu Hamil Terhadap Pelayanan Antenatal di Puskesmas Samata - Anita Rahmiati Bur; Siti Zakiyah (Fatiakara Care: Jurnal Ilmiah Keperawatan, 2026)
Antenatal care (ANC) services are one of the essential efforts to improve maternal and infant health status and to reduce the risk of complications during pregnancy. The knowledge, attitudes, and practices of pregnant women toward antenatal care services play an important role in determining the successful utilization of health services during pregnancy. This study aimed to examine the knowledge, attitudes, and practices of pregnant women toward antenatal care services in the working area of Samata Primary Health Center, Gowa Regency. This research employed a qualitative method with a descriptive approach. The informants in this study consisted of 10 pregnant women as primary informants and 2 midwives as key informants. Data were collected through in-depth interviews, observation, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing, using source and method triangulation to ensure data validity. The results showed that the knowledge of pregnant women regarding the benefits of antenatal care services, Tetanus Toxoid (TT) immunization, iron (Fe) tablet supplementation, and danger signs of pregnancy was generally categorized as adequate. The attitudes of pregnant women toward antenatal care services were also positive as they felt safe and trusted health workers. However, the practices of pregnant women in attending antenatal visits were still varied and not fully in accordance with the minimum standard of antenatal care visits. This indicates that good knowledge and attitudes have not been fully followed by appropriate practices in utilizing antenatal care services. Therefore, continuous health education efforts are needed to encourage pregnant women to attend antenatal care visits according to the recommended standards in order to detect potential complications early.